THE STUDENTS’ DIFFICULTIES IN CHANGING QUOTED SPEECH INTO REPORTED SPEECH IN THE QUESTION FORM - Sari, Suci Hardiyanti Purnama (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
Reported speech is commonly used to report what other people have said or thought without reporting the exact word. However, many students still face some difficulties when changing quoted speech into reported speech in the question form. This study is aimed to know the student’s difficulties and the causes of the difficulties that students have in the transformation. The object of the study is students at batch 2009 in English Department Unlam Banjarmasin. This study uses descriptive method and the population is 112 students. The purposive sampling technique is used to choose sample of study by taking all the students of reg a (50 students) as the sample. To collect the data, the writer uses three instruments. They are written test, questionnaire, and interview. In analyzing the data, some steps are done as follow :( 1) calculating frequency of occurrence of errors in changing quoted question into reported question, (2) making the percentage of students’ difficulties on each area tested, (3) describing the result of questionnaire sheets, (4) interpreting data from interview.           Findings of the study show that the causes of students’ difficulties are they do not understand very well the rule of grammatical change, some of the students do not remember the rule, most of students do not repetition of studying reported speech and almost of all students rarely use reported question form in the real context. Based on the study result, several suggestions are addressed: (1) the lecturers should instruct the students for doing more varieties and meaningful activities during the lesson; (2) it becomes complete when the research involves reported speech in all kind of sentence (statement, command, and question) and the researchers should conduct the test including all aspect in one instruction so they can find in which category, the students had the prominent difficulty.